Recommendations for the treatment of hepatitis C in 2017 - Halota, Waldemar; Flisiak, Robert; Juszczyk, Jacek; Małkowski, Piotr; Pawłowska, Małgorzata; Simon, Krzysztof; Tomasiewicz, Krzysztof (Clinical and Experimental Hepatology, 2017)
The goals of treatment is to eliminate HCV infection, stop or reverse histological changes, reduce the risk of hepatocellular carcinoma development and transmission of the infection to other individuals. According to the recommendation of the Polish Group of Experts for HCV in 2017 all patients with chronic HCV infection should receive treatment, but it is not recommended in patients at high risk of short overall survival. If access to therapy is restricted, priority should be given to patients whose HCV infection can lead to an unfavourable outcome of the disease within a short time frame, particular to individuals with liver cirrhosis, rapidly progressing liver fibrosis, extrahepatic manifestations of HCV infection, chronic kidney diseases, patients before and after organ transplantation. Current recommendations of Polish Group of Experts for HCV provide guidelines to select optimal medication, assessment of liver fibrosis, treatment efficacy, dealing with resistance to direct acting antivirals, monitoring for hepatocellular carcinoma, management of HBV/HCV coinfection and drug interactions. It constains also advice on treatment of special patients populations such as renal failure, liver transplant and hepatic decompensation, as well as retreatment of patients which failed interferon free therapy. Moreover specific recommendations of management patients infected with different genotypes with currently reimbursed regimens or those expected to become available shortly in Poland are also included.